Implementation of E-Government in the Use of the IKD (Digital Population Identity) Application as an Effort to Protect Personal Data at the Kerinci Regency Civil Registry Population Office - Arieska, Arieska (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the Implementation of E-Government in the Use of the IKD (Digital Population Identity) Application as an Effort to Protect Personal Data at the Kerinci Regency Civil Registry Population Office. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results showed that the application of the IKD application based on Permendagri No. 72 of 2022 Article 14, it is known that the application of data technology obtained through interviews with informants by asking questions to state civil apparatus at the Population and Civil Registration Office of Kerinci Regency, has not been maximized in the sense that it has not run as it should and has not met the expected target. For the utilization of digitalization, it can be interpreted that the digital public services provided by the state civil apparatus at the Population and Civil Registration Office of Kerinci Regency are adequate in the sense that they have run as they should and have met the expectations of the community, it can be interpreted that the utilization of digitalization services in the effectiveness of public services at the Dukcapil Office of Kerinci Regency is good in managing population administration. To simplify and accelerate services, it can be interpreted that, IKD can improve and accelerate services at the Population and Civil Registration Office of Kerinci Regency is adequate in the ability to help and provide services quickly and precisely, and responsiveness to consumer desires has met community expectations, it can be interpreted that it has been carried out effectively. In securing IKD data both in playstore and data at the Population and Civil Registration Office of Kerinci Regency, it has been running safely and adequately in the sense that it has been running as it should and has met the expectations of the community.